O legislador educador - Costa, Valquíria Ortiz Tavares (2023)
This study aims to build the concept of an Legislating Educator. First, we seek to understand what political education is. Political education is to bring people knowledge of the practices, values and content necessary to guide their actions both in individual action, in their choice of vote, and in their exercise of citizenship. Its exercise strengthens democracy, as it disseminates its precepts and puts them into action within society. As Plato teaches, the law is the educator of man. The law gives commands, teaches the rules currently in force and, therefore, is the first educator of citizens, which is why it must be elaborated within the greater precepts of the Magna Carta, as it must translate the society that one wants to see implemented. Another evidence of the law’s educational function are the various initiatives taken by the Legislative Power to promote political education, such as courses and visits to learn how legislative activities work. Based on these elements, the concept of Legislating Educator is built, with the present research assuming an exploratory character and with a qualitative methodological approach